Risk factors associated with anemia in pregnant women in a Peruvian health center - Muñoz-Cuadra, Gina Kimberly (2024)
Introduction: Anemia is a significant public health problem, especially in women ofreproductive age. In pregnant women, it can cause serious complications, such aspremature birth. Iron deficiency is a common cause of anemia, so early detectionand treatment is crucial. Objective: To identify risk factors associated with anemia inpregnant women attended at the Ex Fundo Naranjal Health Center in 2022. Materialsand Methods: Cross-sectional observational study of 387 pregnant women attendedbetween July and December 2022. A total of 173 women in the third trimester ofgestation were selected by non-probabilistic convenience sampling. Data wereobtained from prenatal records and analyzed with SPSS 25. Descriptive, bivariate andmultivariate analyses were performed to identify significant associations betweenfactors and anemia. Results: The majority of pregnant women were under 35 yearsof age (84.4%), with basic education (74%) and came from marginal urban areas(79.8%); 36.4% were overweight and 25.4% obese. Multivariate analysis showedthat maternal age under 35 years (adjusted OR 1.18), low education level (aOR 1.14),and not receiving nutritional counseling (aOR 1.03) were significantly associatedwith anemia. Conclusions: Maternal age less than 35 years, low education level andlack of nutritional counselling were significant risk factors for anemia in pregnantwomen. Improved nutrition education and counselling and ensuring adequate ironsupplementation are recommended.